2005
DOI: 10.1007/s10704-005-7151-1
|View full text |Cite
|
Sign up to set email alerts
|

Shock induced void nucleation during Taylor impact

Abstract: Taylor impact experiments in the classic and symmetric configurations were used to study the plastic deformation and void nucleation in Al-6082-T6 rods. Deformation histories during impact were recorded using high-speed photography. X-ray computed tomography was used to visualize the extent of damage in recovered specimens. Above threshold velocities, void nucleation was observed along the central axis of the specimens, and reconstructed images from the tomography provide a 3-D mapping of the damaged region. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…They also showed that different conditions exist for ductile damage development in Taylor anvil and rod-on-rod (ROR) impact tests under equivalent velocity resulting in the fact that ductile damage can develop in ROR while it not necessarily can occur in not overdriven Taylor anvil impact test. Similar results were experimentally observed for other metals, [5,6,7].…”
Section: Introductionsupporting
confidence: 90%
“…They also showed that different conditions exist for ductile damage development in Taylor anvil and rod-on-rod (ROR) impact tests under equivalent velocity resulting in the fact that ductile damage can develop in ROR while it not necessarily can occur in not overdriven Taylor anvil impact test. Similar results were experimentally observed for other metals, [5,6,7].…”
Section: Introductionsupporting
confidence: 90%
“…High-speed optical photography cannot reveal whether or not this actually happens. However, an X-ray technique has recently shown a dimple, rather smaller than indicated in figure 14a, which does indeed form at the interface in symmetric Taylor impact in an aluminium alloy (Chapman et al 2005a).…”
Section: S½t=ð1katþmentioning
confidence: 91%
“…However, the final stress values calculated from the VISAR data exceed this estimate by as much as three to four times, although it should be pointed out that our knowledge of the other properties (e.g. density and wave speed) of the material becomes less certain as it deforms (Addessio et al 1993;Mayes et al 1993;Worswick & Pick 1995;Chapman et al 2005a). There is no sign of any discrete, steep edges due to elastic wave pulses arriving repeatedly at the rod rear, as suggested by Johnson (1972) and Hohler & Stilp (1990), probably because such waves are too dispersed.…”
mentioning
confidence: 88%
“…Based on the work of Chapman and all, the extend of tensile failure inside the specimen comes from the coalescence of radial release waves at the specimen axis [10]. As suggested in this work, simulations conducted with a critical treshold 02024-p.3 pressure appear to be a mean to generate this bulk tensile failure.…”
Section: Numerical Results With a Tensile Failure Criterionmentioning
confidence: 71%